1999
DOI: 10.1080/135467999387324
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Arithmetical Cognition: Performance of Low- and Average-IQ Children

Abstract: Neuropsychological and developmental models of number, counting, and arithmetical skills, as well as the supporting working memory and speed of articulation systems, were used as the theoretical framework for comparing groups of low-and average-IQ children. The low-IQ children, in relation to their average-IQ peers, showed an array of deficits, including difficulties in retaining information in working memory while counting, more problem solving errors, shorter memory spans, and slower articulation speeds. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 54 publications
3
27
0
2
Order By: Relevance
“…The LA and TA children almost always detected these errors, whereas the children with MLD failed to detect them in 1 of 3 trials. The mediational analysis indicated that the failure of children with MLD to detect these errors was fully mediated by the central executive (Hoard et al, 1999). Overall, it appears that children with MLD understand basic counting concepts as well as TA and LA children, and any difficulties that children with MLD have on counting tasks may be due to working memory failures (Klein & Bisanz, 2000).…”
Section: Mathematical Cognition Deficitsmentioning
confidence: 94%
See 1 more Smart Citation
“…The LA and TA children almost always detected these errors, whereas the children with MLD failed to detect them in 1 of 3 trials. The mediational analysis indicated that the failure of children with MLD to detect these errors was fully mediated by the central executive (Hoard et al, 1999). Overall, it appears that children with MLD understand basic counting concepts as well as TA and LA children, and any difficulties that children with MLD have on counting tasks may be due to working memory failures (Klein & Bisanz, 2000).…”
Section: Mathematical Cognition Deficitsmentioning
confidence: 94%
“…These children also fail to detect errors when the first item is double-counted (i.e., the item is tagged one, two) but detect these double-counts when they occur with the last item. The pattern suggests children with MLD understand one-to-one correspondence but have difficulty retaining a notation of the counting error in working memory (Hoard, Geary, & Hamson, 1999). Poor skill at detecting counting errors may compromise ability to correct these errors and thus result in more errors in situations in which counting is used to solve arithmetic problems.…”
Section: Mathematical Development In Children With Mldmentioning
confidence: 99%
“…A more consistent finding is that children with MLD, but not LA children, fail to detect errors when the puppet double counts the first object in an array of objects, that is, this single object is tagged “one,” “two”. They detect these double counts when they occur with the last item, indicating they understand one-one correspondence, but have difficulty retaining a notation of the counting error in working memory during the count (Geary et al, 2004; Hoard, Geary, & Hamson, 1999). The forgetting of miscounts is potentially important for children’s learning to use counting to solve arithmetic problems.…”
Section: Mathematical Cognitionmentioning
confidence: 99%
“…So although there is evidence of how children who struggle in mathematics present normatively and by deficit, there is less evidence of how children who struggle in all aspects of their learning engage with mathematical problems and in particular how knowledge of this engagement can be used by teachers to support learning. Furthermore, there is evidence that children with learning difficulties show similar mathematical performance, in terms of strategy use and learning trajectory, to children without difficulties at a similar stage of mathematical development (Geary, 2004; Gonzalez & Espinel, 2002; Hoard, Geary & Hamson, 1999; Fletcher, Huffman, Bray & Grupe, 1998; Baroody, 1988).…”
Section: Introductionmentioning
confidence: 99%